Angle closure glaucoma in congenital ectropion uvea - Grace M. Wang; Daniel Thuente; Brenda L. Bohnsack (American Journal of Ophthalmology Case Reports, 2018)
Purpose: Congenital ectropion uvea is a rare anomaly, which is associated with open, but dysplastic iridocorneal angles that cause childhood glaucoma. Herein, we present 3 cases of angle-closure glaucoma in children with congenital ectropion uvea. Observations: Three children were initially diagnosed with unilateral glaucoma secondary to congenital ectropion uvea at 7, 8 and 13 years of age. The three cases showed 360° of ectropion uvea and iris stromal atrophy in the affected eye. In one case, we have photographic documentation of progression to complete angle closure, which necessitated placement of a glaucoma drainage device 3 years after combined trabeculotomy and trabeculectomy. The 2 other cases, which presented as complete angle closure, also underwent glaucoma drainage device implantation. All three cases had early glaucoma drainage device encapsulation (within 4 months) and required additional surgery (cycloablation or trabeculectomy). Conclusions and importance: Congenital ectropion uvea can be associated with angle-closure glaucoma, and placement of glaucoma drainage devices in all 3 of our cases showed early failure due to plate encapsulation. Glaucoma in congenital ectropion uvea requires attention to angle configuration and often requires multiple surgeries to obtain intraocular pressure control. Keywords: Congenital ectropion uvea, Juvenile glaucoma, Angle-closure glaucoma, Glaucoma drainage device